Fractional economic models based on market equilibrium in the frame of different type kernelsn - Acay, Bahar; Bas, Erdal; Abdeljawad, Thabet (Pergamon-Elsevier Science Ltd, 2020)
Overall objectives of this paper are to investigate and analyze certain problems in economics by means of non-local fractional operators involving Caputo, Caputo-Fabrizio in the sense of Caputo (CFC), Caputo type Atangana-Baleanu (ABC) and ABC with generalized Mittag-Leffler kernel. By convention, above mentioned fractional operators refer to those beyond traditional differentiation and integration when applying to the economic models. Thereby, these fractional operators improve the comprehension of supply and demand and their interactions with price of commodity under the assumption that market is in equilibrium. Moreover, in order to observe the controversial subjects in market more detailed, we compare the results obtained by supporting with the simulation analysis. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Price adjustment; Time paths; Fractional operators; Economics; Market equilibrium